Space‐Time Characterization and Risk Assessment of Nutrient Pollutant Concentrations in China's Near Seas. Issue 7 (2nd July 2019) - Jiang, Qutu; He, Junyu; Wu, Jiaping; He, Mingjun; Bartley, Evan; Ye, Guanqiong; Christakos, George
Abstract: Human activities interacting with coastal waters lead to large amounts of nutrient loading and severe water pollution in China's near Seas. In this context, a comprehensive quantitative characterization of the spatiotemporal variation of nutrient pollutant concentrations is a key component of any reliable seawater quality assessment and integrated coastal management plan. The present work combines the Bayesian maximum entropy method with stochastic site indicators to estimate monthly nitrate and phosphate concentrations in China's near seas during 2015, explore their spatiotemporal variation, and provide an explicit quantitative assessment of seawater quality in conditions of in situ uncertainty. This makes it the first study of space‐time nutrient pollutant characterization at a national‐scale in a coastal seawater environment. The results showed that nitrate and phosphate distributions exhibit the same spatial trends along China's near seas, whereas high nutrient pollution levels are found in the Yangtze River, Liaohe River, and Pearl River estuaries. Local differences of temporal trends exist between nitrate and phosphate distributions, which suggest that distinct remediation strategies are needed to properly satisfy the required seawater quality standards. The average nitrate and phosphate concentrations across space‐time were found to be equal to 0.271 and 0.015 mg/L, respectively. The nitrate and phosphate concentrations exceeding the fourth grade seawater quality standard during 2015 were about 11% and 2.6%, respectively. The study of both the seasonal changes in human activities along the coastal cities and the temporal marine hydrodynamics can offer a better understanding of the seawater quality and the biogeochemical process of nutrient transport and distribution. Key Points: Bayesian maximum entropy maps showed that nitrate and phosphate concentrations had similar spatial distributions Nitrate and phosphate distributions exhibited different seasonal patterns that may have been affected by coastal hydrodynamics and human activities Stochastic site indicators showed that nitrate pollution was much more serious than phosphate pollution